Europejskie Nauczycielskie Studia Magisterskie (EMETT) – moduły interkulturowe - Niżegorodcew, Anna (Neofilolog, 2010)
This paper is first of all informative. In the first section, it gives a survey of innovative Master Studies for European secondary teachers, being prepared by an international team from eight countries. Among five main training areas, there are Intercultural Studies, which are to be implemented in another country during a mobility semester. The second section of the paper describes briefly four intercultural modules developed in the EMETT Studies: Education systems in the European Union, Intercultural communication, Selected aspects of European culture and Intercultural education. The third part of the paper gives an example of the teaching material which can be used to raise students’ intercultural awareness. The material is based on a literary text made into a contemporary play, focused on the universal theme of a journey, set in the Polish Tatra Mts. The author of the paper shows how such a material can combine elements of three intercultural modules: Intercultural education, Intercultural communication and Selected aspects of European culture. Finally, the paper points out the role of a language of international communication in the implementation of EMETT Studies during the mobility semester.